Frequency distribution of cytokine and associated transcription factor single nucleotide polymorphisms in Zimbabweans: Impact on schistosome infection and cytokine levels - Hanton, Andrew John; Scott, Fiona; Stenzel, Katharina; Nausch, Norman; Zdesenko, Grace; Mduluza, Takafira; Mutapi, Francisca (PLOS Neglected Tropical Diseases, 2022)
Author summary Cytokines are known to modulate the course of infections and immune pathologies, the production of which is partly under genetic control. Genetic variation, such as single nucleotide polymorphisms (SNPs), are therefore known to influence phenotypes in infectious diseases. This study sought to understand how SNPs in genes encoding cytokines and associated transcription factors influence susceptibility and immune responses to schistosomiasis. Here, we report a range of SNPs upregulating immune responses being highly frequent among our Zimbabwean sample, and in addition identify two novel infection-associated loci. Firstly, the IL4 SNP rs2070874 T allele was identified as protective, while the IFNG SNP rs2069727 G allele was identified as a risk allele. Given the paucity of genetic studies focussing on African populations and neglected tropical diseases, our study provides a valuable contribution to our knowledge of the genetic control of schistosomiasis susceptibility with these findings. In addition, we highlight the role of genetics in modulating balance in immune responses and emphasise that further research focussing on African populations is required on this subject in order to improve our understanding of genetics, immune responses, and neglected diseases.